(untitled) (Damascus University Journal of agriculture sciences, 2023)
This research was done in the laboratories of Food Science Department- College of Agriculture - Damascus University and Biotechnology - Ministry of Higher Education during 2020- 2021. The aim of this research is to determine the optimum conditions for the extraction of stevioside glycoside using three types of solvents (water - pure ethanol - ethanol 80%) at different levels of temperature (30-60-90° C), and different times (30-60-90 minutes). Using a statistical design (RSM) response surface methodology. The results show that the best conditions for extracting Stevia rebaudiana glycoside using water as a solvent were at a temperature of 90° C, and for a time of 30 minutes, with a maximum concentration (12.83%), followed by ethanol 80% at a temperature of 90° C, and for a time of 50 minutes and a maximum concentration (%9.80), and then pure ethanol at a temperature of 90 °C and over a time of 90 °C, where the value of the glycoside value was (6.84%).